A BRIEF OF REVIEW OF EMS IMPLEMENTATION IN UNIVERSITY CAMPUS - Filson Maratur Sidjabat; Riri Asyahira Sariati Syah; Michelle Natasya Gunawan (Teknik Lingkungan Universitas Islam Indonesia, 2020)
Higher education institutions has a huge population that induces the large consumption of drinking water, the large consumption of electricity, the production of large quantities of garbage, the use of high transport and the rise in the building of facilities. Thus the implementation of Environmental Management System in Unversity Campus is crucial to achieve sustainability campus. This study is a literature review about the implementation of the ISO 14001 Environmental Management System in University campus and its recommendation. The discussion also discussed its implementation in indonesia’s campus as well as in other country campus. The implementation have to be done is start from environmental policy that made by campus adjusting to the ISO 14001 , the environmental management planning , implementation , and assessment for evaluation. Several campus has been implementing environmental management system but still need improvement. Universities should start implementing environmental management practices that promotes sustainable development and protection of the environment. These initiatives can focus on various environmental aspects, depending on the needs and culture of the campus. Although some case studies have shown that the solid waste management is a common aspect that many institutions focus on.